A review on the historical development of the lift-type vertical axis wind turbine: From onshore to offshore floating application. (April 2020) - Hand, Brian; Cashman, Andrew
Highlights: The development of the lift-type VAWT is studied from inception to present. The VAWT development has not been smooth and has experienced many setbacks. The VAWT is receiving a resurgence of attention for the offshore floating industry. Abstract: This paper discusses the historical evolution of the lift-type vertical axis wind turbine (VAWT) since its inception in the early 1930s. The VAWT received almost no development until the early 1970s when engineers in Canada and the USA began to study the VAWT design as a source of generating electricity. Many curved-bladed VAWTs were tested and are reviewed in this paper. Separately, the straight-bladed VAWT was developed by researchers in the UK and is also discussed. This review highlights that the VAWT received very little engineering development in the 1990s due to dominance of the HAWT in the wind energy market. Although, the literature also indicates that the VAWT has entered a Renaissance period whereby the VAWT is now being adopted for the offshore floating wind turbine industry. The latest developments in the floating VAWT technology and attempts to commercialise this technology have been documented.